2013
DOI: 10.30539/iraqijvm.v37i1.340
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Fertile Estrus in Bitches using Equine Chorionic Gonadotropine (eCG) and Human Chorionic Gonadotropine (hCG)

Abstract: Eighteen (18) anestrous bitches aged 3-6 years were used in this study. They were diagnosed clinically by external and vaginal examination and the bitches were divided randomly into three equal groups (6 bitches). The 1st group were treated I/M with 20 IU eCG / bitch for 6 days with single injection and 150 IU of hCG hormone /Bitch on day 7 . The 2nd group were treated I/M with 30 IU eCG / bitch for 6 days with single injection and 150 IU of hCG hormone /bitch on day 7, and the 3rd group were treated I/M with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…Our findings were agreed those recorded by some researchers [12] who found that the pregnancy rate was 75% in all groups treated with eCG / hCG. In addition, our findings were consistent with findings of other researchers.…”
Section: Resultssupporting
confidence: 93%
“…Our findings were agreed those recorded by some researchers [12] who found that the pregnancy rate was 75% in all groups treated with eCG / hCG. In addition, our findings were consistent with findings of other researchers.…”
Section: Resultssupporting
confidence: 93%
“…Also, an independent t-test was used to compare the two means. Statistical significance was defined as P < 0.05 (Al-Hamedawi, 2013).…”
Section: Discussionmentioning
confidence: 99%